2013
DOI: 10.1186/1748-717x-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Integration method of 3D MR spectroscopy into treatment planning system for glioblastoma IMRT dose painting with integrated simultaneous boost

Abstract: BackgroundTo integrate 3D MR spectroscopy imaging (MRSI) in the treatment planning system (TPS) for glioblastoma dose painting to guide simultaneous integrated boost (SIB) in intensity-modulated radiation therapy (IMRT).MethodsFor sixteen glioblastoma patients, we have simulated three types of dosimetry plans, one conventional plan of 60-Gy in 3D conformational radiotherapy (3D-CRT), one 60-Gy plan in IMRT and one 72-Gy plan in SIB-IMRT. All sixteen MRSI metabolic maps were integrated into TPS, using normaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 34 publications
2
112
0
Order By: Relevance
“…29 Patients with adverse prognostic factors defined by age or performance status or both are now commonly treated with hypofractionated RT, e.g., 40 Gy in 15 fractions. 30 In the elderly, this is now the preferred regimen for patients with tumors lacking MGMT promoter methylation. 23,31 Neither accelerated hyper-nor hypofractionated regimens nor brachytherapy nor radiosurgery or a stereotactic RT boost have been shown to be superior to standard fractionation in terms of survival.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…29 Patients with adverse prognostic factors defined by age or performance status or both are now commonly treated with hypofractionated RT, e.g., 40 Gy in 15 fractions. 30 In the elderly, this is now the preferred regimen for patients with tumors lacking MGMT promoter methylation. 23,31 Neither accelerated hyper-nor hypofractionated regimens nor brachytherapy nor radiosurgery or a stereotactic RT boost have been shown to be superior to standard fractionation in terms of survival.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…However, larger criterion of 3%, 3 mm was assessed because clinically we utilize a 3% + 3 mm as our range uncertainty for proton plans. Also, this criterion for gamma analysis is utilized for IMRT QA and gives some clinical reference regarding the acceptability of comparing two different dose planes 13, 14, 15, 16. Plans were evaluated at treatment isocenter in the coronal, sagittal, and transverse planes.…”
Section: Methodsmentioning
confidence: 99%
“…Those that do are either limited to one room only with specific adaptations for a CT such as a “track” solution or cone‐beam CT (CBCT). An alternative to mobile helical CT scanners for image‐guided proton therapy is the gantry‐mounted cone‐beam CT (CBCT) 5, 6, 7, 8, 9. Gantry‐mounted CT systems may provide more convenience than mobile scanners.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent SBRT studies showed local control rates and toxicity profiles were comparable to the conventional dose regimen of 2 Gy per fraction (2 Gy/Fx) 2, 3. It has been reported that with a prescription dose of 7.25 Gy/Fx or higher in SBRT treatment planning, margins are usually 5 mm or smaller to spare the surrounding organs at risk such as rectum, urethra, and bladder 1.…”
Section: Introductionmentioning
confidence: 99%